1999
DOI: 10.1002/ijch.199900030
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen‐Bond Rearrangement and Intermolecular Proton Transfer in Protonated Methanol Clusters

Abstract: Vibrational predissociation spectra (VPS) of hydrogen‐bonded and non‐hydrogen‐bonded (free) OH stretches within the frequency range of 2700–3800 cm−1 are closely analyzed to determine the isomeric structures and proton location in protonated methanol clusters, H+(CH3OH)n. The present report emphasizes protonated methanol tetramers and pentamers, which are predicted by ab initio calculations to exist in linear and cyclic forms. Only one isomer with linear structure was identified in the VPS of protonated methan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2002
2002
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 41 publications
4
22
0
Order By: Relevance
“…The observed IR spectra of n = 4 and 5 are essentially the same as those reported by Chang et al , They demonstrated that the IR spectral feature of n = 4 and 5 shows a temperature dependence, which indicates the presence of the cyclic and linear chain isomers. The present IR spectra are similar to those measured under the higher internal temperature condition of Chang et al, and both of the isomers may contribute to the spectra.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The observed IR spectra of n = 4 and 5 are essentially the same as those reported by Chang et al , They demonstrated that the IR spectral feature of n = 4 and 5 shows a temperature dependence, which indicates the presence of the cyclic and linear chain isomers. The present IR spectra are similar to those measured under the higher internal temperature condition of Chang et al, and both of the isomers may contribute to the spectra.…”
Section: Resultssupporting
confidence: 84%
“…As for the protonated methanol, H + (MeOH) n , experimental information on the hydrogen bond structure is very limited, despite its importance as a model of the proton solvation by molecules other than water. Chang et al carried out IR spectroscopy of the clusters of n = 4 and 5. , While a linear chain structure was predominant for n = 4, the coexistence of the linear chain and the cyclic form was found for n = 5. They suggested that the interconversion between the linear and cyclic forms causes a fast intracluster proton transfer.…”
Section: Introductionmentioning
confidence: 99%
“…The enthalpy and entropy effects were investigated using temperature studies by Yamdagni and Kebarle and by Meot-Ner and co-workers in proton-transfer equilibria of diamines and triamines, , protonated polyethers and crown ethers, , and diketones. , Studies by the McMahon and Stone groups found similar effects in dialcohols, , amino alcohols, and methoxy alcohols. , The cyclic internally bonded structures were confirmed by ab initio calculations on diamines, polyethers, methoxy alcohols, ,, and other molecules and also confirmed by H 2 O and MeOH loss through metastable and collisional dissociation . Cyclic iIHB structures and solvent effects thereon were confirmed also by recent IR predissociation spectroscopy studies, especially by the group of Y. T. Lee and co-workers. ,, …”
Section: Complex Molecules:  Intramolecular and Multiple Bondsmentioning
confidence: 86%
“…IR spectroscopy of such ions for n =4,5 has been reported and a linear chain conformation is suggested to be the predominant structure for n = 4, and the coexistence of linear chain and cyclic structures is suggested for n = 5 clusters. 15,16 For larger ͑MeOH͒ n H + , n = 4 -15, IR spectroscopy of the OH stretch region has shown that the free OH stretch feature decreases in intensity with increasing n and finally disappears at n =7. 17 This report suggests that a bicyclic hydrogen bonded structure is appropriate for ͑MeOH͒ n H + , n Ͼ 7.…”
Section: Introductionmentioning
confidence: 99%